Xeroderma Pigmentosum: Ocular Findings in an Isolated Brazilian Group with an Identified Genetic Cluster. (31st October 2019) - Schelini, Maria Claudia; Chaves, Luis Fernando O. B.; Toledo, Marcia C.; Rodrigues, Francisco W.; de Oliveira, Tauan; Isaac, David L. C.; Avila, Marcos
Abstract : Purpose . Xeroderma pigmentosum (XP) is a rare autosomal recessive genetic disorder characterized by increased susceptibility to UV radiation- (UVR-) induced skin pigmentation, skin cancers, ocular surface disease, and, in some patients, sunburn and neurological degeneration. Eight different genes are affected, and the prevalence of the disease differs across the world. The present study describes the main ophthalmologic features and symptoms in patients with XP in this case series. Methods . Patients were examined consecutively at the University Hospital of the Federal University of Goias between January 2016 and June 2018. All patients underwent ophthalmologic examination and were asked about their ophthalmological history and the presence of ocular symptoms. Results . Twenty-one patients with genetic confirmation were evaluated. The genetic variants XPV and XPC were detected in the patients. The most prevalent findings include eyelid changes, observed in 80.9% of the patients, and ocular surface changes as punctate keratopathy, occurring in 16 patients (76.2%), corneal neovascularization, and corneal opacities. Six patients (28.5%) presented corneoconjunctival tumor. More than half of patients had previous history of treatment of ocular neoplasia. Ocular burning was the most reported symptom. Conclusions . The ocular characteristics identified in this study corroborate the existing literature, mainly related to the surface. Concerning the XP variant and the gravity of ocular signs, XPC has earlier and more severe symptoms than XPV. Due to their relative rarity, publications of XP cases are important to understand the possible damages caused by the disease in the eyes and surrounding area.